SOFTWARE DESIGN IN STOREY BUILDINGS - Poppy Widiastuti; Drs. Soebijantoro MMEng (Jurnal Sistem Komputer, 1997)
Building Automation System is a system that is used to control and monitor the equipment that existed at the storied building. Equipment commonly monitored as generator, chiller, pumps, AHU, lighting and so forth. To be more efficient in controlling the equipment, we need a planned program schedule will be easier to turn off or turn off the equipment. Schedule this program will control the lighting devices located on 9th floor of the basement until the chiller and control devices which only four are on the floor. All this equipment is planned to be lit on each day at 7:05 and off at 17:30 pm